INTERTEXTUAL STUDY THROUGH FILMS AS AN AID FOR STUDENTS TO UNDERSTAND ENGLISH NOVELS - Muniroch, Sri (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
Understanding English literary works is evitably a big problem for the students of non-English-speaking countries. The writer proposes that intertextuality may help the students to understand them better. Through her study, she tries to find out the problems the students have in understanding literary works, in this case, novels; and to investigate how intertextual study through films can help them to solve the problems. By doing observation and interview to the students in her class of English Prose, she finds out that the problems are the difficulty to understand the sense of the language, the cultural gap, the uncontextuality with their experience, the difficulty to grasp the imagery, and the lack of information about the literary works. Through the films adapted from the novels they read, the students can overcome their problems. The films make them understand the sense of the language, understand the culture, more aware of the relation among people and the situation, feel that they become part of the issues in their lives, get more vivid images about the setting, the characters and other elements, familiar with the issues in the works. All of them help them to understand more the novels they are reading.Keywords: Intertextuality, Film Adaptation